Relevance of expandable titanium cage for the treatment of cervical spondylotic myelopathy - Zaïri, Fahed (Springer-Verlag, 2012)
BACKGROUND: In patients with cervical spondylotic myelopathy, ventral disease and loss of physiological cervical lordosis are indications for anterior approach. As bone graft and titanium cage present many drawbacks, expandable titanium cage has been recently introduced for this indication. The authors present the clinical and radiological outcomes in patients undergoing the placement of an expandable cage in the treatment of spondylotic myelopathy with straight or kyphotic cervical spine alignment. METHODS: This was a retrospective review of prospectively collected data. A total of 26 patients underwent cervical corpectomy and reconstruction using an expandable titanium cage and anterior plate between 2005 and 2008. Pain and functional disability were measured using VAS and mJOA preoperatively and at 3 months, 6 months, 1 year and 2 years. Kyphosis was measured using lateral radiographs at the same points of follow-up. Fusion was evaluated on flexion–extension radiographs at 2 years. RESULTS: The mean VAS improved from 4.2 to 1.7 and the mean mJOA increased from 12.85 to 16.04 at 2 years postoperatively (p < 0.05). The mean kyphosis angle decreased from 17° to 2° at the last follow-up (p < 0.05). The fusion rate was 100 % at 2 years. Three complications were reported including a transient dysphagia, an epidural hematoma and an early hardware migration. CONCLUSION: Expandable titanium cage is an effective device, which achieves good clinical and radiological outcomes at a minimum 2-year follow-up.